UNVEILING THE GREEN TREASURE TROVE TO UNLOCKING SUSTAINABILITY : EXPLORING THE VALUE OF GREEN INTELLECTUAL CAPITAL AND GREEN ACCOUNTING - Niken Safitri; Tuti Setiatin; Rizal Zaelani; Muhammad Zaky; Ebah Suaebah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
With the increasing awareness of environmental issues and the need for sustainability, companies around the world are increasingly paying attention to the environmental impact of their activities. In this context, the concepts of green accounting and green intellectual capital emerge as important frameworks for measuring and managing environmental impacts and are able to contribute to corporate sustainability. This literature study includes an analysis of various relevant literature sources from several databases such as Elsevier, Emerald and Spingers in the last 5 years using an inclusive technique. The resulting sample was 16 studies consisting of 10 articles on GIC and 6 articles on GA. The focus of this study is to understand the concepts of green accounting and green intellectual capital, and their implications in the context of business sustainability. The results show that green accounting enables companies to measure, monitor and report the environmental impacts of their operations more accurately. Meanwhile, green intellectual capital plays an important role in enhancing a company's competitiveness and innovation through the sustainable management of intellectual capital